Pemantauan dan Pengendalian Kepekatan Larutan Nutrisi Hidroponik Berbasis Jaringan Sensor Nirkabel - Helmy Helmy; Aji Rahmawati; Syahrul Ramadhan; Thomas Agung Setyawan; Arif Nursyahid (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
Nutrient Film Technique (NFT) is one of hydroponic plant cultivation models. Most of hydroponic farmers are using NFT model to raise the productivity of crops. NFT hydroponic farmers usually use more than one hydroponic table in order to fulfill market needs. Harvest failures can happen when farmers do not have suficient information on monitoring and controlling the nutrition solution concentration. This can be overcome with the existence of monitoring and controlling system of nutrition solution concentration. This paper aims to build and examine system reliability using two NFT hydroponic tables based on wireless sensor network. Each table is installed with monitoring and controlling of nutrition solution concentration devices which transmit the data to server throughwireless sensor network. The result shows that electrical conductivity meter which is used to read nutrition solution concentration has 3.92% of error rate. Node 2 has faster threshold data transmission than node 1, with 34.68 second of node 2 delay and 40.01 second of node 1 delay. Node 1 has better accuracy of nutrition solution concentration control for 96.12% than node 2 which has 92.79% nutrition solution concentration accuracy.